PERSEPSI GURU IPA SMP NEGERI KOTA PEKANBARU TERHADAP KETERLAKSANAAN PENDIDIKAN KARAKTER DAN HOTS (HIGHER ORDER THINKING SKILLS) - Mardatilla, Mardatilla; Suryawati, Evi; Yustina, Yustina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Realizing a more meaningful learning process in the 2013 curriculum the government issued several regulations that contained several school programs in the form of character education implementation, and HOTS (Higher Order Thinking Skills). The purpose of this study was to analyze the perceptions of junior high school science teachers on the feasibility of character education, and HOTS in state junior high school Pekanbaru. This research is a descriptive study conducted in July to September 2018. The sample in this study was 45 grade VII science teachers from state junior high school Pekanbaru who were selected by Purposive Sampling. The instruments used were questionnaires and observation sheets. All closed questionnaire items were declared valid and reliable with alpha equal to 0.938 in very good criteria. Data obtained by distributing questionnaires, interviews and direct observation. The data obtained were analyzed descriptively, obtained the following results: The implementation of character education based on the results of data analysis and observations that have been carried out is in very good criteria with an average of 4.3 based on the linkert scale. The effectiveness of Higher Order Thinking Skills (HOTS) based on the results of the questionnaire answers and observations has not been implemented properly.Key Words: Character education, HOTS, Science teacher